2017
DOI: 10.1039/c7py01391d
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pendant group structure on the thermoresponsive properties of N-substituted polyesters

Abstract: Structure–property correlation studies of a diverse set of biodegradable thermoresponsive polyesters provides a rationale for the design of thermoresponsive polyesters with desired cloud points.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 45 publications
2
21
0
Order By: Relevance
“…The clear-turbid phase transition occurred before and after cloud point temperature (T cp ) [19][20][21][22][23]. The polymer hydration is thus wrapped by water molecules and dissolves when the temperature is lower than T cp .…”
Section: Introductionmentioning
confidence: 99%
“…The clear-turbid phase transition occurred before and after cloud point temperature (T cp ) [19][20][21][22][23]. The polymer hydration is thus wrapped by water molecules and dissolves when the temperature is lower than T cp .…”
Section: Introductionmentioning
confidence: 99%
“…35 The inherent oxymethylene moieties of these polymers exhibit the properties like abovementioned amide linkages. N-Succinamide polyesters (HESA polyesters) 36 have been developed as biodegradable thermoresponsive polymers. Another promising strategy to introduce thermoresponsive property into polymers is to modify the side chains of the polymer with multiple oligoethylene glycol (OEG) chains.…”
Section: Reviewmentioning
confidence: 99%
“…We base this study on our previously reported serendipitous discovery that a library of thermoresponsive polyesters designed in our lab show 'tropoelastin-like' coacervation behavior. [18][19][20] Tropoelastin, the soluble precursor to elastin, shows lower critical solution temperature (LCST) in aqueous medium, and above LCST, the protein solution segregates to both dilute and proteinrich dense phases. [21] Similarly, our polyester library also shows hydrophobically-driven, single component coacervation.…”
mentioning
confidence: 99%
“…[21] Similarly, our polyester library also shows hydrophobically-driven, single component coacervation. Their non-ionic, bioabsorbable, [19] cell-compatible, [20] and modular nature, allows incorporation of various functional groups [18] and hence this platform provides significant advantages over any other reported coacervates to date. In this study, we report an extension of the above polyesters, wherein incorporation of appropriate functional groups provides a new class of non-ionic, self-coacervating polyesters that demonstrate rapid, watertolerant crosslinking, resulting in strong underwater adhesion.…”
mentioning
confidence: 99%
See 1 more Smart Citation